Soft magnetic iron alloy plate and its manufacturing method
Patent Information
- Application Number
- JP2021041372
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-03-15
AI Technical Summary
【0016】 本発明によれば、パーメンジュールに匹敵する飽和磁束密度および電磁純鉄と同等の鉄損を有し、かつパーメンジュールよりも低コストの軟磁性鉄合金板およびその製造方法を提供することができる。
Smart Images

Figure 0007629764000002 
Figure 0007629764000003 
Figure 0007629764000004
Abstract
Description
[Technical field]
[0001] The present invention relates to magnetic material technology, and more particularly to a soft magnetic iron alloy plate having a higher saturation magnetic flux density than an electromagnetic pure iron plate, and a method for manufacturing the same. [Background technology]
[0002] Magnetic steel sheets and magnetic pure iron sheets (for example, 0.01 to 1 mm thick) are materials used as the iron cores of rotating electrical machines and transformers by laminating and molding multiple sheets. For iron cores, it is important that the conversion efficiency between electrical energy and magnetic energy is high, so high magnetic flux density and low iron loss are important. To increase the magnetic flux density, it is desirable for the material to have a high saturation magnetic flux density Bs, and Fe-Co alloy materials and iron nitride martensite materials are known as iron-based materials with high Bs.
[0003] Needless to say, reducing the cost of the iron core is one of the most important issues, and technological development to stably and inexpensively manufacture materials with high Bs has been actively pursued for some time.
[0004] For example, Patent Document 1 (JP 2020-132894 A) discloses a plate- or foil-shaped soft magnetic material having a high saturation magnetic flux density, which contains iron, carbon, and nitrogen, and includes martensite containing carbon and nitrogen and γ-Fe, in which a nitrogen-containing phase is formed in the γ-Fe.
[0005] According to Patent Document 1, a soft magnetic material that has a saturation magnetic flux density exceeding that of pure iron and has thermal stability can be manufactured at low cost and used to improve the characteristics of magnetic circuits of electric motors, etc., thereby enabling miniaturization of electric motors, etc., and increasing torque, etc. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2020-132894 A Summary of the Invention [Problem to be solved by the invention]
[0007] Among currently commercially available soft magnetic materials, permendur (49Fe-49Co-2V mass% = 50Fe-48Co-2V atomic%) is well known as the material with the highest Bs. However, the material cost of Co, although it varies depending on the market conditions, is 100 to 200 times higher than the material cost of Fe, so permendur has the disadvantage of being a very expensive material. In other words, in Fe-Co alloy materials, if the Co content is reduced, the material cost can be reduced accordingly.
[0008] However, Fe-Co alloy materials have a weakness in that Bs also decreases when the Co content is reduced. It is possible to compensate for the decrease in Bs caused by a decrease in the Co content by forming iron nitride martensite, but it is difficult for nitrogen atoms to penetrate and diffuse into Fe-Co alloy materials, making it difficult to form iron nitride martensite, and no method has been established for forming iron nitride martensite in Fe-Co alloy materials.
[0009] Furthermore, when elements that promote the penetration and diffusion of nitrogen atoms (e.g., Al, Cr, Mo, Nb) are added to Fe-Co alloy materials in order to generate iron nitride martensite, another problem occurs in that Bs decreases further and iron loss Pi increases.
[0010] On the other hand, in the case of iron cores for rotating electrical machines (for example, motors and generators), in addition to high Bs and low Pi, mechanical strength (for example, tensile strength) that can withstand rotational centrifugal force is also an important requirement.
[0011] In recent years, there has been a strong demand for small, high-output rotating electrical machines, and improving the properties of the core is an urgent issue. As mentioned above, reducing the cost of the core is naturally one of the most important issues.
[0012] Therefore, an object of the present invention is to provide a soft magnetic iron alloy sheet having a saturation magnetic flux density comparable to that of permendur and an iron loss equivalent to that of electromagnetic pure iron, and which is less expensive than permendur, and a manufacturing method thereof. [Means for solving the problem]
[0013] (I) One aspect of the present invention is a soft magnetic iron alloy plate, A chemical composition containing 0 atomic % or more and 30 atomic % or less of cobalt (Co), 0.1 atomic % or more and 11 atomic % or less of nitrogen (N), 0 atomic % or more and 1.2 atomic % or less of vanadium (V), with the balance being iron (Fe) and impurities; The soft magnetic iron alloy plate has a surface region having an average nitrogen concentration of 1 atomic % or more and 15 atomic % or less in a thickness direction thereof, and an inner region having an average nitrogen concentration lower than the average nitrogen concentration of the surface region, The soft magnetic iron alloy plate is characterized in that the surface region has a thickness of 1% to 30% from both main surfaces of the soft magnetic iron alloy plate, and in that iron nitride martensite having a tetragonal crystal structure is generated.
[0014] In the present invention, the surface layer region is defined as the outermost layer region including the main surface along the thickness direction of the steel plate, and the inner region is defined as the region sandwiched between the surface layer regions.
[0015] (II) Another aspect of the present invention is a method for producing the above-mentioned soft magnetic iron alloy sheet, a starting material preparation step of preparing a starting material made of a soft magnetic material containing Fe as a main component and 0 atomic % or more and 30 atomic % or less of Co and having a thickness of 0.01 mm or more and 1 mm or less; a nitrogen immersion heat treatment process in which the starting material is heated and quenched in a predetermined ammonia (NH3) gas atmosphere to cause 1 atomic % or more and 15 atomic % or less of N to penetrate and diffuse into a surface layer region of the starting material; A sub-zero treatment step of cooling the starting material that has been subjected to the nitrogen immersion heat treatment step to 0°C or lower, The present invention provides a method for producing a soft magnetic iron alloy sheet, characterized in that the nitriding heat treatment process includes a nitriding process of heating the starting material while controlling the nitriding potential in the atmosphere within a predetermined range, and a cooling process of quenching the starting material to less than 100°C at a cooling rate of 100°C / s or more while controlling the nitriding potential in the atmosphere within a predetermined range. Effect of the Invention
[0016] According to the present invention, it is possible to provide a soft magnetic iron alloy sheet having a saturation magnetic flux density comparable to that of permendur and an iron loss equivalent to that of electromagnetic pure iron, and which is less expensive than permendur, and a manufacturing method thereof. [Brief description of the drawings]
[0017] [Figure 1] 1 is a process diagram showing an example of a method for producing a soft magnetic iron alloy plate according to the present invention. [Figure 2A] 1 shows the results of N concentration quantitative analysis in the plate thickness direction for a cross section of Example 1, and an X-ray diffraction pattern for a surface of Example 1. [Figure 2B] 1 shows the results of N concentration quantitative analysis in the plate thickness direction for a cross section of Comparative Example 1, and an X-ray diffraction pattern for the surface of Comparative Example 1. [Figure 2C] 1 shows the results of N concentration quantitative analysis in the plate thickness direction for a cross section of Comparative Example 2, and an X-ray diffraction pattern for the surface of Comparative Example 2. [Diagram 3] 1 shows the results of N concentration quantitative analysis in the plate thickness direction for a cross section of Example 2, and an X-ray diffraction pattern for a surface of Example 2. [Figure 4] 13 shows the results of quantitative analysis of N concentration in the thickness direction for a cross section of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] In the present invention, the following improvements and modifications can be made to the soft magnetic iron alloy plate (I) described above. (i) The average nitrogen concentration in the surface region is higher than the average nitrogen concentration in the inner region by 0.5 atomic % or more. (ii) The internal region is mainly composed of a ferrite phase having a cubic crystal structure. (iii) the inner region has an average nitrogen concentration of less than 1 atomic %. (iv) The saturation magnetic flux density is 2.2 T or more, and the core loss under the condition of a magnetic flux density of 1.0 T and 400 Hz is less than 50 W / kg.
[0019] In the present invention, the following improvements and modifications can be made to the above-mentioned manufacturing method (II) of a soft magnetic iron alloy sheet. (v) the nitriding potential K N is the NH3 gas partial pressure P in the NH3 gas atmosphere NH3 and hydrogen (H2) gas partial pressure P H2 From "K N =P NH3 / P H2 3 / 2 " and "0.001 atm -1 / 2 ≦K N ≦10 atm -1 / 2 " is controlled so that
[0020] The present inventors have conducted extensive research into a method for forming iron nitride martensite by infiltrating and diffusing nitrogen atoms into an Fe-Co alloy sheet. As a result, they have found that iron nitride martensite can be effectively formed in the surface layer region of an Fe-Co alloy sheet by setting the Co content at 30 atomic % or less, controlling the nitriding potential during nitrous heat treatment within a predetermined range, and controlling the cooling rate during cooling. It has been confirmed that the obtained Fe-Co alloy sheet has a saturation magnetic flux density comparable to that of permendur and an iron loss equivalent to that of electromagnetic pure iron, despite the reduced Co content. The present invention has been completed based on this finding.
[0021] Hereinafter, the embodiments of the present invention will be described in detail along with the manufacturing procedure with reference to the drawings. However, the present invention is not limited to the embodiments described here, and can be appropriately combined with known techniques or improved based on known techniques within the scope of the technical idea of the invention. In addition, in this specification, the case where an Fe-Co alloy plate is used as the starting material will be described in detail, but even if an Fe foil that does not contain Co is used as the starting material, it is possible to achieve both high saturation magnetic flux density and low iron loss by providing a difference in average nitrogen concentration between the surface layer region and the inner region.
[0022] Fig. 1 is a process diagram showing an example of a method for producing a soft magnetic iron alloy sheet according to the present invention. As shown in Fig. 1, the method for producing a soft magnetic iron alloy sheet according to the present invention generally includes a starting material preparation step S1, a nitrous heat treatment step S2, and a sub-zero treatment step S3. The nitrous heat treatment step S2 includes a nitrous process S2a and a cooling process S2b. Each step will be described in more detail below.
[0023] In the starting material preparation step S1, a plate material (thickness 0.01 to 1 mm) containing Fe as the main component (the component with the highest content rate) and Co at 0 atomic % to 30 atomic % is prepared as the starting material. By setting the Co content at 30 atomic % or less, N can penetrate and diffuse, and the material cost can be significantly reduced compared to permendur. The Co content is preferably 3 atomic % to 30 atomic %, more preferably 5 atomic % to 25 atomic %, and even more preferably 8 atomic % to 20 atomic %.
[0024] Although not an essential component, V may be contained within 4% of the Co content (for example, when Co=30 atomic %, V≦1.2 atomic %). There is no particular limitation on the means for the starting material preparation step S1, and a known method can be used as appropriate. Commercially available products may also be used.
[0025] In addition, impurities (impurities that may be contained in the starting material, such as H (hydrogen), B (boron), C (carbon), Si (silicon), phosphorus (P), sulfur (S), chromium (Cr), manganese (Mn), nickel (Ni), copper (Cu), etc.) are permitted within a range that does not have a significant adverse effect on the Bs of the soft magnetic iron alloy plate (for example, a total concentration of 2 atomic % or less).
[0026] Next, in the nitrous heat treatment step S2, a nitrous heat treatment is performed to cause N to penetrate into the surface layer region of the prepared starting plate material. The nitrous heat treatment in the present invention comprises a nitrous process S2a in which the nitriding potential is controlled within a predetermined range and heating is performed, and a cooling process S2b in which the nitriding potential is controlled within a predetermined range and the cooling rate is controlled. The greatest feature of the manufacturing method according to the present invention is the nitrous heat treatment step S2.
[0027] In the nitrogen immersion process S2a, nitrogen is introduced and diffused to a desired N concentration at a temperature of 500°C or higher (for example, in the austenite phase (γ phase) formation temperature range) in a specified ammonia gas atmosphere. As the ammonia gas atmosphere, a mixed gas of NH3 gas and N2 gas, a mixed gas of NH3 gas and Ar gas, or a mixed gas of NH3 gas and H2 gas can be suitably used.
[0028] In addition, the nitriding potential during the nitrous heat treatment step S2 is controlled within a predetermined range. NH3 and hydrogen gas partial pressure P H2 From the nitriding potential K N "K N =P NH3 / P H2 3 / 2 " and "0.001 atm -1 / 2 ≦K N ≦10 atm -1 / 2 The NH3 gas flow rate, the carrier gas (N2 gas, Ar gas, H2 gas) flow rate, and the total pressure in the heat treatment furnace are controlled so that the total pressure in the heat treatment furnace is preferably 0.4 atm or higher.
[0029] It is preferable to introduce NH3 gas after the temperature reaches 500°C or higher. This is because if NH3 gas is actively introduced in the stable temperature range of the ferrite phase (α phase), the N As the temperature rises, the desired tetragonal structure of the iron nitride phase (FeN phase (α' phase) and / or Fe 16 This is because undesirable iron nitride phases (for example, Fe4N phase (γ' phase) and Fe3N phase (ε phase)) are more likely to form than undesirable iron nitride phases (for example, Fe4N phase (γ' phase) and Fe3N phase (ε phase)).
[0030] Temperature, time and K in nitrogen immersion process S2a N By controlling the above, it is possible to control the thickness and N concentration of the surface region (high N concentration layer) where nitrogen penetrates and diffuses. The soft magnetic iron alloy sheet as a whole contains 0.1 atomic % to 11 atomic % of nitrogen. The average N concentration of the surface region that becomes the high N concentration layer is preferably 1 atomic % to 15 atomic %, more preferably 2 atomic % to 11 atomic %.
[0031] The thickness of the surface region (high N concentration layer) is preferably controlled to 1% to 30% from each of the two main surfaces of the sheet material. In other words, the inner region of the sheet material is preferably a low N concentration layer (average N concentration <1 atomic %) where nitrogen has not penetrated and diffused, and the average N concentration is more preferably 0.5 atomic % or less.
[0032] The iron nitride martensite (α' phase and / or α" phase) with a tetragonal structure generated in the subsequent cooling process S2b has crystal lattice distortion caused by the intrusion of nitrogen atoms, which contributes to improving Bs. On the other hand, the α' phase and α" phase have a weakness in that Pi is easily increased due to increased magnetocrystalline anisotropy. In contrast, the iron alloy sheet of the present invention has an internal region made of a ferrite phase (α phase) with a low N concentration, making it possible to suppress the increase in Pi throughout the iron alloy sheet.
[0033] In addition, it is preferable that a part of the surface region (high N concentration layer) forms a nitrogen concentration transition region (average concentration gradient is 0.1 atomic % / μm or more and 10 atomic % / μm or less) in which the N concentration decreases toward the inner region (low N concentration layer). The formation of a N concentration gradient makes it easier for the magnetization state (magnetic domains and magnetization) in the α' phase and / or α" phase with high N concentration to propagate to the α phase with low N concentration. As a result, the overall coercive force becomes smaller, which contributes to reducing Pi.
[0034] In the nitrogen immersion process S2a, nitrogen is introduced and diffused to the desired N concentration. N While maintaining the temperature, a cooling process S2b is performed in which the temperature is rapidly cooled to less than 100°C. The cooling rate at this time is preferably 100°C / s or more, more preferably 200°C / s or more, and even more preferably 400°C / s or more. This produces the desired iron nitride martensite with a tetragonal crystal structure. If the cooling rate is less than 100°C / s, the undesired iron nitride phase is likely to be produced.
[0035] Also, K N If the cooling process S2b is performed without maintaining this condition, a denitrification phenomenon occurs in which the nitrogen that has penetrated into the surface layer region is released, making it difficult to generate the iron nitride phase itself.
[0036] By the cooling process S2b, most of the austenite phase (γ phase) can be transformed into martensite structure, but some γ phase may remain (residual γ phase). Since the γ phase is non-magnetic, it is preferable that the volume fraction of the residual γ phase is 5% or less from the viewpoint of magnetic properties.
[0037] Therefore, in order to transform the residual γ phase into a martensite structure, it is preferable to perform a sub-zero treatment step S3 (e.g., ordinary sub-zero treatment using dry ice or ultra-sub-zero treatment using liquid nitrogen) in which the material is cooled to below 0°C after the cooling process S2b.
[0038] Although not an essential step, a tempering step S4 at 100° C. or more and 210° C. or less may be further carried out after the subzero treatment step S3 in order to impart toughness to the soft magnetic iron alloy sheet (not shown in FIG. 1).
[0039] As explained above, by quenching a sheet material containing Fe as the main component and 30 atomic % or less of Co, after nitrogen is introduced and diffused only into the surface region, a composite is obtained in which the surface region is a phase having high Bs and high mechanical strength, and the inner region is a phase having small magnetocrystalline anisotropy. As a result, the soft magnetic iron alloy sheet of the present invention exhibits high Bs, low Pi, and high mechanical strength. EXAMPLES
[0040] The present invention will be explained in more detail below with reference to various experiments, however, the present invention is not limited to the configurations and structures described in these experiments.
[0041] [Experiment 1] (Preparation of starting material 1) Commercially available pure metal raw materials (Fe, Co, each with a purity of 99.9%) were mixed and an alloy ingot was produced by arc melting on a water-cooled copper hearth (manufactured by Daia Vacuum Co., Ltd., automatic arc melting furnace, in a reduced pressure Ar atmosphere). At this time, in order to homogenize the alloy ingot, the sample was turned over and remelted six times. The obtained alloy ingot was pressed and rolled to prepare an 80 at.% Fe-20 at.% Co alloy plate (thickness = 0.07-0.09 mm) as starting material 1.
[0042] [Experiment 2] (Preparation of soft magnetic iron alloy plates of Example 1 and Comparative Examples 1 and 2) Three types of nitrogen immersion heat treatment with different cooling processes were performed on the starting material 1 prepared in Experiment 1. The nitrogen immersion process involved introducing NH3 gas when the temperature reached 500°C, with a total pressure of 0.8 atm and a nitriding potential of ≒ 4 atm. -1 / 2 The test was performed in an NH3 gas atmosphere at 500°C for 2 hours, and then at 900°C for 1 hour.
[0043] Cooling process 1: Nitrogen immersion process followed by NH3 gas atmosphere (total pressure = 0.8 atm, nitriding potential ≒ 4 atm) -1 / 2While maintaining the specimen temperature, the specimen was subjected to water quenching / water quenching by dropping it into water at room temperature (20°C) (average cooling rate ≒ 400°C / s). The NH3 gas atmosphere was then replaced with N2 gas atmosphere, and the specimen was subjected to ultra-subzero treatment by immersing it in liquid nitrogen within 5 minutes from the start of quenching (start of cooling process), thereby transforming the residual γ phase into a martensite structure. This sample is designated as Example 1.
[0044] Cooling process 2: After replacing the NH3 gas atmosphere with N2 gas atmosphere at 900℃, the specimen was dropped into water at room temperature (20℃) for water quenching / water quenching (average cooling rate ≒ 400℃ / s). After that, while maintaining the N2 gas atmosphere, the specimen was immersed in liquid nitrogen within 5 minutes from the start of quenching (start of cooling process) for ultra-subzero treatment, transforming the residual γ phase into a martensite structure. Cooling process 2 differs from cooling process 1 in the atmosphere during cooling. This sample is referred to as Comparative Example 1.
[0045] Cooling process 3: After holding at 900°C for 1 hour in the nitrogen immersion process, the specimen was subjected to gas quenching / gas quenching by spraying N2 gas at room temperature (20°C) onto the specimen (average cooling rate ≒ 80°C / s). After that, while maintaining the N2 gas atmosphere, the specimen was immersed in liquid nitrogen within 5 minutes from the start of quenching (start of the cooling process) for ultra-subzero treatment, transforming the residual γ phase into a martensite structure. Cooling process 2 has a different cooling rate from cooling process 1. This sample is referred to as Comparative Example 2.
[0046] [Experiment 3] (Investigation of the composition of the soft magnetic iron alloy plates of Example 1 and Comparative Examples 1 and 2) The cross sections of the soft magnetic iron alloy plate samples (Example 1 and Comparative Examples 1 and 2) produced in Experiment 2 were subjected to quantitative analysis of N concentration in the plate thickness direction using an electron probe microanalyzer (JXA-8800RL, manufactured by JEOL Ltd., spot diameter 2 μm).
[0047] In addition, wide-angle X-ray diffraction measurements (WAXD) using Cu-Kα radiation were performed on the surfaces of the soft magnetic iron alloy plate samples (Example 1 and Comparative Examples 1 and 2) to identify the detected phases. The X-ray diffraction device used was a Rint-Ultima III manufactured by Rigaku Corporation. The results are shown in Figures 2A to 2C.
[0048] FIG. 2A shows the results of N concentration quantitative analysis in the plate thickness direction for the cross section of Example 1, and an X-ray diffraction pattern for the surface of Example 1.
[0049] As shown in Fig. 2A, in Example 1, the quantitative analysis of N concentration in the sheet thickness direction confirmed that a high N concentration layer was formed in the surface region, a low N concentration layer existed in the internal region, and an N concentration transition region was formed in a part of the surface region. In addition, the XRD pattern for the surface confirmed that the α phase (ferrite phase) was the main phase, and the α' phase (iron nitride martensite with a tetragonal crystal structure) was generated. The γ phase (austenite phase) and γ' phase (Fe4N phase) were hardly detected.
[0050] From these findings, it is believed that the nitrogen immersion process forms a high N concentration layer in the surface region, while the cooling process produces the α' phase, and that the sub-zero treatment leaves almost no residual γ phase. Also, since the α phase is the main phase in the XRD pattern, it is believed that the high N concentration layer in the surface region is not entirely α' phase, but is in a mixed phase state of α and α' phases.
[0051] FIG. 2B shows the results of N concentration quantitative analysis in the plate thickness direction for the cross section of Comparative Example 1, and an X-ray diffraction pattern for the surface of Comparative Example 1.
[0052] As shown in Fig. 2B, in Comparative Example 1, the quantitative analysis of N concentration in the thickness direction confirmed that a high N concentration layer was not formed in the surface region, and that a low N concentration layer was formed throughout the thickness direction. In addition, only the α phase was confirmed from the XRD pattern of the surface.
[0053] From these findings, it is confirmed that if the atmosphere in the cooling process deviates from the conditions of the present invention, denitrification occurs and the high N concentration layer in the surface region cannot be maintained.
[0054] FIG. 2C shows the results of N concentration quantitative analysis in the plate thickness direction for the cross section of Comparative Example 2, and an X-ray diffraction pattern for the surface of Comparative Example 2.
[0055] 2C, in Comparative Example 2, the quantitative analysis of N concentration in the sheet thickness direction confirmed that a high N concentration layer was formed in the surface region, a low N concentration layer existed in the internal region, and an N concentration transition region was formed in part of the surface region, similar to Example 1. However, the XRD pattern for the surface confirmed peaks of the α phase and the γ' phase (Fe4N phase), but no peak of the α' phase was detected.
[0056] From these facts, it is considered that when the cooling rate in the cooling process deviates from the conditions of the present invention, the formation of the α' phase by martensitic transformation does not occur, and the γ' phase, which is closer to a thermal equilibrium state, is formed.
[0057] [Experiment 4] (Preparation of soft magnetic iron alloy plate of Example 2) The starting material 1 prepared in experiment 1 was subjected to a nitrogen immersion heat treatment different from that in experiment 2. In the nitrogen immersion process, NH3 gas was introduced at the stage where the temperature reached 1000°C, and the total pressure was 0.8 atm and the nitriding potential was ≒ 4.3 atm. -1 / 2 The cooling process was carried out under the condition that the NH3 gas atmosphere was kept at 1000°C for 2 hours with a total pressure of 0.8 atm and a nitriding potential of ≒ 4.3 atm. -1 / 2 Except for the above, the cooling process was carried out in the same manner as in the cooling process 1 of Experiment 2. This sample is designated as Example 2.
[0058] (Investigation of the composition of the soft magnetic iron alloy plate of Example 2) In the same manner as in Experiment 3, quantitative analysis of N concentration in the sheet thickness direction was performed by EPMA on the cross section of Example 2, and detection phases were identified by XRD on the surface of Example 2. The results are shown in FIG.
[0059] FIG. 3 shows the results of N concentration quantitative analysis in the plate thickness direction for the cross section of Example 2, and an X-ray diffraction pattern for the surface of Example 2.
[0060] 3, it is confirmed that a high N concentration layer is formed in the surface region, a low N concentration layer exists in the internal region, and an N concentration transition region is formed in a part of the surface region in Example 2, similarly to Example 1. In addition, from the XRD pattern of the surface, it is confirmed that the α phase is the main phase and the α' phase is generated.
[0061] From the results of Experiments 2 to 4, it is confirmed that the key points of the manufacturing method of the soft magnetic iron alloy sheet according to the present invention are the nitriding process S2a (a process of heating while controlling the nitriding potential within a predetermined range) and the cooling process S2b (a process of controlling the nitriding potential within a predetermined range and controlling the cooling rate) in the nitriding heat treatment step S2.
[0062] [Experiment 5] (Preparation of soft magnetic iron alloy plate of Comparative Example 3) A commercially available electromagnetic pure iron plate (thickness = 0.1 mm) was prepared. In the nitrogen immersion heat treatment, NH3 gas was introduced at the stage where the temperature reached 750°C, and the total pressure was 1 atm and the NH3 partial pressure P NH3 =1×10 4 Pa and N2 partial pressure P N2 =2×10 4 The test was performed under the condition that the specimen was held at 750°C for 5 hours in an NH3 gas atmosphere of 10 Pa. The cooling process was performed by oil quenching in which the specimen was dropped into oil at 60°C while maintaining the same NH3 gas atmosphere. The NH3 gas atmosphere was then replaced with an N2 gas atmosphere, and the specimen was immersed in liquid nitrogen within 5 minutes of the start of quenching (the start of the cooling process) for ultra-subzero treatment, thereby transforming the residual γ phase into a martensite structure. This sample is designated Comparative Example 3.
[0063] (Investigation of the composition of the soft magnetic iron alloy plate of Comparative Example 3) In the same manner as in Experiment 3, quantitative analysis of N concentration in the plate thickness direction was performed by EPMA on the cross section of Comparative Example 3. The results are shown in FIG.
[0064] Fig. 4 shows the results of quantitative analysis of N concentration in the sheet thickness direction for the cross section of Comparative Example 3. It is confirmed that Comparative Example 3 has a structure in which a high N concentration layer is uniformly formed along the sheet thickness direction, and a low N concentration layer or a N concentration transition layer does not exist. This is considered to be because Comparative Example 3 does not have Co components, which are an inhibitor of N penetration and diffusion.
[0065] [Experiment 6] (Investigation of the characteristics of the soft magnetic iron alloy sheets of Examples 1-2 and Comparative Examples 1-4) The characteristics of the various soft magnetic iron alloy sheets thus produced were investigated. At this time, starting material 1 (a sample that was not subjected to the nitrogen immersion heat treatment) was used as Comparative Example 4 as a standard for the characteristics.
[0066] The magnetic properties were measured as saturation magnetic flux density Bs and core loss Pi. The magnetization (unit: emu) of the sample was measured under conditions of a magnetic field of 1.6 MA / m and a temperature of 20°C using a vibrating sample magnetometer (Riken Denshi Co., Ltd. BHV-525H), and Bs (unit: T) was calculated from the sample volume and mass. In addition, the Pi of the sample was measured under conditions of a magnetic flux density of 1.0 T, 400 Hz, and a temperature of 20°C using the H coil method using a BH loop analyzer (IFG Co., Ltd., IF-BH550) and a vertical yoke single sheet tester. -1.0 / 400 (Unit: W / kg) was measured.
[0067] As mechanical properties, the tensile strength of some samples was measured using a universal material testing machine. In addition, the Vickers hardness (Hv) of the sample surface was measured using a micro Vickers hardness tester (Matsuzawa Co., Ltd., AMT-X7AFS) (load: 25 gf, holding time: 20 seconds, average of 5 points). For the Vickers hardness test, commercially available non-oriented electrical steel sheet and permendur sheet were separately prepared as comparison samples.
[0068] The magnetic properties and tensile strength results are shown in Table 1.
[0069] [Table 1]
[0070] As shown in Table 1, Examples 1 and 2 according to the present invention show higher Bs than Comparative Examples 1 to 4, and it is confirmed that they have a high Bs comparable to that of permendur, even though the Co content is less than half that of permendur. -1.0 / 400 Regarding this, in Examples 1 and 2, there is almost no adverse effect due to the high N concentration layer, and the iron loss is almost the same as that of the electromagnetic pure iron sheet.
[0071] It was confirmed that the tensile strength of Example 2, which has iron nitride martensite in the surface layer region, is significantly improved compared to Comparative Example 4, which was not subjected to nitrous heat treatment. In addition, the Vickers hardness of Example 2 was 218 Hv. From this, it was confirmed that the soft magnetic iron alloy sheet of the present invention has a hardness equivalent to that of commercially available non-oriented electrical steel sheets and permendur sheets, and is considered to show the same workability as those conventional materials.
[0072] The above-mentioned embodiments and experiments are described to aid in understanding of the present invention, and the present invention is not limited to the specific configurations described. For example, it is possible to replace a part of the configuration of the embodiments with a configuration according to the technical common sense of a person skilled in the art, and it is also possible to add a configuration according to the technical common sense of a person skilled in the art to the configuration of the embodiments. In other words, it is possible to delete, replace, or add a part of the configuration of the embodiments or experiments in this specification without departing from the technical idea of the invention.
Claims
1. A soft magnetic iron alloy plate, A chemical composition comprising 3 atomic % or more and 30 atomic % or less of cobalt, 0.1 atomic % or more and 11 atomic % or less of nitrogen, 0 atomic % or more and 1.2 atomic % or less of vanadium, with the balance being iron and impurities; The soft magnetic iron alloy plate has a surface region having an average nitrogen concentration of 1 atomic % or more and 15 atomic % or less in a thickness direction thereof, and an inner region having an average nitrogen concentration lower than that of the surface region, The surface region has a thickness of 1% to 30% from both main surfaces of the soft magnetic iron alloy plate, and a ferrite phase and iron nitride martensite having a tetragonal crystal structure are generated, with an austenite phase being 5 volume % or less.
2. The soft magnetic iron alloy plate according to claim 1, A soft magnetic iron alloy plate, characterized in that the average nitrogen concentration in the surface region is 0.5 atomic % or more higher than the average nitrogen concentration in the inner region.
3. The soft magnetic iron alloy plate according to claim 2, A soft magnetic iron alloy plate, characterized in that the inner region is mainly composed of a ferrite phase having a cubic crystal structure.
4. The soft magnetic iron alloy plate according to claim 2 or 3, A soft magnetic iron alloy plate, characterized in that the average nitrogen concentration in the internal region is less than 1 atomic %.
5. The soft magnetic iron alloy plate according to any one of claims 1 to 4, The saturation magnetic flux density is 2.3 T or more. A soft magnetic iron alloy plate having an iron loss of less than 50 W / kg under conditions of a magnetic flux density of 1.0 T and 400 Hz.
6. A method for producing a soft magnetic iron alloy plate, comprising the steps of: The soft magnetic iron alloy plate is A chemical composition comprising 0 atomic % or more and 30 atomic % or less of cobalt, 0.1 atomic % or more and 11 atomic % or less of nitrogen, 0 atomic % or more and 1.2 atomic % or less of vanadium, with the balance being iron and impurities; The soft magnetic iron alloy plate has a surface region having an average nitrogen concentration of 1 atomic % or more and 15 atomic % or less in a thickness direction thereof, and an inner region having an average nitrogen concentration lower than that of the surface region, The surface layer region has a thickness of 1% to 30% from both main surfaces of the soft magnetic iron alloy plate, and a ferrite phase and iron nitride martensite having a tetragonal crystal structure are generated, and an austenite phase is 5 volume % or less, The manufacturing method includes: a starting material preparation step of preparing a starting material having a thickness of 0.01 mm to 1 mm, the starting material being made of a soft magnetic material containing iron as a main component and 30 atomic % or less of cobalt; a nitrous heat treatment process in which the starting material is heated and quenched in a predetermined ammonia gas atmosphere to cause 1 atomic % or more and 15 atomic % or less of nitrogen to penetrate and diffuse into a surface layer region of the starting material; A sub-zero treatment step of cooling the starting material that has been subjected to the nitrogen immersion heat treatment step to 0°C or lower, The nitriding heat treatment step includes a nitriding process of heating the starting material while controlling the nitriding potential in an atmosphere within a predetermined range, and a cooling process of quenching the starting material to less than 100°C at a cooling rate of 100°C / s or more while controlling the nitriding potential in the atmosphere within a predetermined range.
7. In the method for producing a soft magnetic iron alloy sheet according to claim 6, The nitridation potential K N is the ammonia gas partial pressure P NH3 and hydrogen gas partial pressure P H2 From "K N =P NH3 / P H2 3 / 2 " and "0.001 atm -1 / 2 ≦K N ≦10 atm -1 / 2 " A method for manufacturing a soft magnetic iron alloy plate, characterized by controlling the temperature so that "
Citation Information
Patent Citations
Manufacture of iron nitride magnetic material having superior corrosion resistance and high saturation magnetization
JP1987017132A
Manufacture of bulk alpha'' iron nitride with high saturated magnetic flux density
JP1991244108A
Production of magnetic strip having high saturating magnetization
JP1992268027A
High hardness high magnetic property steel and its production method
JP2005226116A
Soft magnetic material, method for producing the same and electric motor using soft magnetic material
JP2020132894A